PACAP/GCGa Is an Important Modulator of the Amphioxus CNS-Hatschek’s Pit Axis, the Homolog of the Vertebrate Hypothalamic-Pituitary Axis in the Basal Chordates - On, Jason S. W.; Su, Liuru; Shen, Hong; Arokiaraj, Aloysius W. R.; Cardoso, João C. R.; Li, Guang; Chow, Billy K. C. (Frontiers in Endocrinology, 2022)
The Hatschek’s pit in the cephalochordate amphioxus, an invertebrate deuterostome basal to chordates is suggested to be the functional homologue structure of the vertebrate hypothalamus, adenohypophysis and neurohypophysis based on anatomy and expression of homologous neuroendocrine genes. However, the endocrine potential of the cephalochordate Hatschek’s pit remains to be demonstrated as well as the physiological actions of the secreted neuropeptides. In this study, we have explored the distribution and characterize the potential function of the amphioxus PACAP/GLUC precursor, which is the orthologue of the hypothalamic PACAP neuropeptide in vertebrates. In amphioxi, two PACAP/GLUC transcripts PACAP/GLUCa and PACAP/GLUCbc that are alternative isoforms of a single gene with different peptide coding potentials were isolated. Immunofluorescence staining detected their expression around nucleus of Rohde, supporting that this structure may be homologous of the neurosecretory cells of the vertebrate hypothalamus where abundant PACAP is found. PACAP/GLUCa was also detected in the infundibulum‐like downgrowth approaching the Hatschek’s pit, indicating diffusion of PACAP/GLUCa from the CNS to the pit via the infundibulum‐like downgrowth. Under a high salinity challenge, PACAP/GLUCa was upregulated in amphioxi head and PACAP/GLUCa treatment was found to increase expression of GHl in Hatschek’s pit in a dose-dependent manner, suggesting that PACAP/GLUCa may be involved in the regulation of GHl via HP-like axis in a similar manner than in vertebrates. Our results support that the amphioxus Hatschek’s pit is likely to be the functional homologue of pituitary gland in vertebrates.